Fluxos turbulentos de CO2 em uma área de arroz irrigado no RS - Carneiro, Janaína Viário (2007)
This thesis quantifies the net change of CO2 (NEE) in an irrigated rice crop cultivation in RS (Brazil). The research is part of the project CT-HIDRO, which presents as main purpose the description of surface conditions for different ecosystems in the country. Data were gathered during the cultivation period, from October 2003 to March 2004. During this time, the average air temperature and the incident radiation were suitable for the development of the culture in such an area. The turbulent flows, calculated by the eddy covariance method, overestimated the NEE value, probably due to the low estimate of breathing tax, because, during some night-times, sensor registered little turbulence. Moreover, other factor could have interfered in the result of the flows, for instance, the time in which the flows are calculated. The Webb correction was applied in the curve of NEE, and a value smaller than 1% was found. Such result didn't modify the previous result significantly. The behavior of CO2 flow during the whole analyzed period showed a maximum of -0,47mgCO2 m−2 s −1 in January 2004, what demonstrates the largest absorption of CO2 from the atmosphere by the plant during the day and a smaller liberation at night, due to the development phase in which the plant is. In this case, the Webb correction was also little emphasized, not interfering in the obtained result. The curves that demonstrate the three phases of development of the rice presented a larger absorption of CO 2 during the reproductive phase. The behavior of the flow of CO 2 showed a negative flow during the day, when the plant absorbs CO2 from the atmosphere, and a positive flow during the night, when the inverse process occurs, what was waited for. The latent heat flow presented larger diary average values from January to February, always with positive values, consequence of the rice crop irrigation. Two days with high values of flow of latent heat were obtained, what motivated the analysis of the energy balance. The closing of the energy balance was not reached in both days. A possible reason for that could be the low estimate of flows when the eddy covariance method was applied.